Making a narrative tourism map: the case of Jiaxing’s ‘Red Boat Spirit Map’, China - Lingqi Wang; Jiangyue Zhang; Min Weng; Mengjun Kang; Shiliang Su (Journal of Maps)
Today, the marriage between cartographic language and narrative strategies has reshaped maps with the generative capability to represent the intangible historical characters and events involved in social memories following a narrative manner. Despite these advances, rather few efforts have been spared to unveil the potential of tourism maps in a narrative form. This paper seeks to rectify the gaps in this line of research by unfolding the underlying theories and cartographic design guidelines for making narrative tourism maps. In particular, a narrative cartographic design approach is demonstrated and evidenced to be practical using the case of ‘Red Boat Spirit Map’, a tourism map designed for Jiaxing City, one of the most well-known destinations of China’s red tourism. It is believed that the theoretical instrument and cartographic design guidelines presented in our paper are particularly relevant and can be easily adapted to more general research of narrative maps.